Accidental dexmedetomidine overdose in preterm newborns: a report of 3 cases - Giulia Paviotti; Mariabeatrice D’Agostini; Isabella Mauro; Federica Bortolotti; Rossella Gottardo; Carla Pittini (Italian Journal of Pediatrics)
Abstract Background Dexmedetomidine use in neonatal units is increasing. Data on its safety are still limited. There are no previous reports of clinical presentation of dexmedetomidine overdose in newborns. Case presentation Three babies simultaneously developed a similar clinical picture of recurrent apneas, a typical “gasping” breathing pattern, irritability followed by hypotonia and hyporeactivity, hyperglycaemia, hypocapnia, increase in lactates and a suppression-burst pattern on CFM/EEG. Babies required intubation and mechanical ventilation due to poor respiratory effort. Symptoms resolved completely in a few hours. Dexmedetomidine was administered enterally by a nasogastric tube in place of caffeine due to “look alike” medication error. Dexmedetomidine was retrieved in biological samples. Babies were developing regularly at post-discharge follow up visits. Conclusion Dexmedetomidine overdose due to medication error is possible in newborns and should be suspected in case of clinical presentations similar to the one we reported. Measures should be implemented in neonatal units for a safe use of dexmedetomidine.